'Fuzzy and context dependent': a critical discourse analysis of manipulation in online vaccine information. Issue 1 (2nd January 2023) - Elkin, Lucy E; Stubbe, Maria H.; Pullon, Susan R.H.
ABSTRACT: In health decision-making, the distinctions between manipulation, persuasion and coercion are easily blurred. Manipulation, viewed through a bioethics lens is problematic only when it affects a person's ability to make autonomous decisions. In contrast, in critical discourse analysis (CDA), manipulation usually has negative connotations. This article uses childhood MMR (measles, mumps and rubella) vaccine information as a case study in manipulative discourse. Online vaccine information across three organisations was analysed using CDA methodology. Each organisation used manipulative discourse in their vaccine information but with varying degrees of transparency. The less transparent an organisation's motivations are, the less compatible it is with autonomous decision-making. This paper argues for adding further nuance to how discursive manipulation is defined within CDA, particularly in the field of public health. In this setting, manipulation is not necessarily immoral or unfair, but it may be, depending on whether it controls a person's ability to make an autonomous, informed decision.